In situ crystallization of highly conducting and transparent ITO thin films deposited by RF magnetron sputtering. (October 2016) - Aijo John, K.; Philip, Rachel Reena; Sajan, P.; Manju, T.
Abstract: ITO thin films are prepared on glass substrates by radio frequency magnetron sputtering at sputtering powers varying from 50W to 200W. Structural and morphological investigation by X-ray diffraction and scanning electron microscopy of the films reveals them to have progressively undergone in situ crystallization with increasing sputtering power, without any need of intentional substrate heating. This result is highly useful in applications where ITO film coatings are to be fabricated on substrates which cannot withstand high temperature. Further, the preferential orientation of the thin film planes along [100] direction is found to produce drastic enhancements in the carrier mobility and electrical conductivity without much affecting the transparency of the thin films. Highlights: In situ Crystallization of ITO films without post deposition annealing. Electrically tunable ITO films by simple one step fabrication method. Useful method of crystallization for substrates such as polymers with weak thermal resistance.